Integrated proteome and phosphoproteome analysis of gastric adenocarcinoma reveals molecular signatures capable of stratifying patient outcome. Issue 2 (29th December 2022) - Lu, Xue; Fu, Yunyun; Gu, Lei; Zhang, Yunpeng; Liao, Antony Y.; Wang, Tingting; Jia, Bin; Zhou, Donglei; Liao, Lujian
Abstract : Metastasis is one of the main causes of low survival rate of gastric cancer patients. Exploring key proteins in the progression of gastric adenocarcinoma (GAC) may provide new candidates for prognostic biomarker development and therapeutic intervention. We applied quantitative mass spectrometry to compare the proteome and phosphoproteome of primary tumor tissues between GAC patients with and without lymph node metastasis (LNM). We then performed an integrated analysis of the proteomic and transcriptomic data to reveal the molecular features. We quantified a total of 5536 proteins, and we found 218 upregulated and 49 downregulated proteins in tumor samples from patients with LNM compared to those without LNM. Clustering analysis identified a number of hub proteins that have been previously shown to play important roles in gastric cancer progression. We also found that two extracellular proteins, TNXB and SPON1, are overexpressed in patients with LNM, which correlates with poor survival of GAC patients. Overexpression of TNXB and SPON1 was validated by western blotting and immunohistochemistry. Furthermore, treating gastric cancer cells with anti‐TNXB antibody significantly reduced cell migration. Finally, quantitative phosphoproteomic analysis combined with activity‐based kinase capture revealed a number of activated kinases in primary tumor tissues from patients with LNM, among which GSK3 might be a new target that warrants further study. Our study provides a snapshot of the proteome and phosphoproteome of GAC tumor tissues that have metastatic potential, and identifies potential biomarkers for GAC progression. Abstract : We conducted an integrated proteomic analysis of primary tumor tissues from gastric adenocarcinoma (GAC) patients. We discovered overexpression of TNXB and SPON1 in patients with lymph node metastasis, which correlates with poor survival of GAC patients. Inhibiting TNXB function using specific antibody significantly reduced gastric cancer cell migration. Phosphoproteomic analysis combined with activity‐based kinase capture revealed abnormal activation of GSK3.